Filippo Vassalli and the Purge From Fascism (Italian Review of Legal History, 2024)
The essay, set in the tumultuous and confused period following the fall of fascism, is divided into two parts: the first part reconstructs the involvement of Filippo Vassalli, an eminent professor and highly esteemed lawyer, in the purges from fascism of the University of Rome. At first he was called to be part of the University’s Purification Committee, but he refused the appointment. Later, he was included among those who could be purged and the High Commissioner for Sanctions against Fascism referred him to the Commission for the Purification of University Personnel. He dropped all the charges with a careful and precise defense brief and the Commission for the Purification of University Personnel acquitted him.The second part of the essay examines, instead, the lengthy process through which Vassalli, initially alone, defended senators declared deposed by the High Court of Justice for sanctions against fascism, to rehabilitate people he considered worthy of esteem and respect, in no way comparable to fascist hierarchs. Declaring his intention to avoid any political controversy, he strictly adhered to legal categories and he assumed that the sanction imposed on the senators had a criminal nature. So he based the first six appeals on article 528 of the Criminal Procedure Code, that admitted “at any time” the extraordinary appeal to the Supreme Court in United Sections [Corte di Cassazione a Sezioni Unite] against convictions by special judges. In this way, he circumvented the prohibition of appeals against the decisions of High Court. The Criminal United Sections of the Supreme Court, with an order dated January 15, 1946, declared them inadmissible, but, an ambiguous phrase seemed not to completely close the possibility of judicial review in a different venue.The new scenarios opened up by the exceptional judicial event attracted the attention of several prominent jurists, sparking a lively debate.In the period following the Supreme Court’s order rejecting the appeals, there were many changes in the political and legal context: in fact, the dominance of the radical left had gradually been replaced by that of the democratic center, and after the excesses of the “wild purge”, the path of civil pacification had been taken. Vassalli resumed the initiative in defence of a good number of senators, but this time other lawyers also took action and they all submitted appeals to the Civil United Sections of Supreme Court, pivoting on article 362 of the Civil Procedure Code, which allowed appeals to the Supreme Court “at any time” against the judgments of special judges for reasons pertaining to their jurisdiction.The judges of the Civil United Sections of the Supreme Court reached an agreement with great difficulty and the decision was taken with only one majority vote. With sentence dated July 9, 1946, they accepted the claim based on the excess of power committed by the High Court. All the contested orders were therefore overturned for absolute lack ofjurisdiction of the special judge who had issued them.The sentence provoked the reaction of the judge who had presided over the High Court, Lorenzo Maroni. To defend his actions, he wrote in an article in “la Giustizia Penale” that he had carried out his assignment only in the interest of the Nation, “for higher requirements of domestic and foreign policy”.The judge reasoned from a perspective of political expediency, very far from that strictly legal chosen by Vassalli, and he asserted that the deposition orders issued by the HighCourt constituted “the exercise of a power carried out in the constitutional sphere for unquestionably political purposes” and they should be removed from any review by thejudicial authority.After the sentence of the United Civil Sections, other appeals were filed both by senators who had not yet taken action and by the heirs of deceased senators, but the outcomes were not always favorable: in fact, the judges considered that the deposition orders motivated by the adhesion to the Republic of Salò, i. e. “to the government of nationalbetrayal and civil war”, were fully valid, as they contained a specific and very serious charge, and those appeals were rejected.Despite this final partial defeat, Vassalli had shown that even in the exceptional circumstances and in the general disorientation of post-fascist Italy, the reasons of politics had to remain anchored to the solid reference point that only the law could provide, because the rebuilding of democratic institutions could not disregard the basic principles of civil coexistence.
Keywords: Filippo Vassalli; purge; fascism; Senators; High Court of Justice for sanctions against fascism